ANALISIS PENGARUH BUDAYA ORGANISASI, MOTIVASI, DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI Studi di PT. Pegadaian (Persero) Cabang Kota Pangkalpinang - Meritania; Sitepu, Mimpin; Medinal (Jurnal Progresif Manajemen Bisnis, 2018)
Independent variables used by researchers are Organizational Culture, Motivation, and Leadership as well as the dependent variables as performance developed by themselves according to the indicators in each variable. This study uses quantitative analysis of primary data which includes the results of the researcher's performance directly in the field. The tool used by researchers for statistical data processing using SPSS 22 program. The results of research from researchers showed that: First, there is a significant influence of the Organizational Culture variable on Employee Performance (0.05) of 2.04841. Thus thitung (3.073)ae in PT. Pegadaian (Persero) Branch of Pangkalpinang City. This is evidenced by the t-count of 3.073 while the t-table with degrees of freedom 28 on > (0.05) of 2.04841. Thus t-hitung (3.330) t-table (2.04841), so Ho is clearly rejected and H1 accepted or if see the sign value of 0.001. Second, there is a significant influence of motivation variables on Employee Performance in PT. Pegadaian (Persero) Branch of Pangkalpinang City. This is evidenced by the value of t count of 3.330 while the t-table with degrees of freedom 28 on > t-table (2.04841), so Ho is clearly rejected and H1 accepted or if see the sign value of 0.002 Thus t-hitung (0.540)> t-table (2.04841), so Ho is clearly rejected and H1 accepted or if see the sign value of 0.010. Fourth, Of the three variables, studied namely Organizational Culture, Motivation, and Leadership together have a significant influence on Employee Performance in PT. Pawnshop (Persero) Branch of Pangkalpinang City. This is proved by the value of Fhitung of 3.573 while the Ftable value of 2.98 thus Fcount (3,573)> Ftable (2.98). Based on the results of the research above researchers, it can be concluded that the performance of PT. Pegadaian (Persero) Branch Pangkalpinang City will increase if using 3 (three) variables through Organizational Culture, Motivation, and Leadership.